Involvement of Serum Matrix Metalloproteinase-9 in the Pathogenesis of Acute Myocardial Infarction - Tserendavaa, Sumiya; Enkhtaivan, Odkhuu; Cho, Jung Rae; Lee, Namho; Chuluunkhuu, Gandulam; Shagdar, Zorigoo; Malchinkhuu, Munkhzol (Central Asian Journal of Medical Sciences, 2016)
Objectives: Prior studies indicate that matrix metalloproteinase-9 (MMP-9) plays a key role in pathogenesis of plaque rupture. The objective of this study was to evaluate the involvement of serum MMP-9 enzyme at pathogenesis of the plaque rupture in coronary atherosclerosis. Methods: The study enrolled 80 consecutive patients who underwent percutaneous coronary intervention in our institution. Inclusion in the case group (n = 40) required a ruptured coronary atherosclerotic plaque confirmed by conventional angiography, whereas inclusion in the control group (n = 40) required stable coronary atherosclerosis. Serum MMP-9 levels were determined by ELISA. Cardiac Infarction Injury Score (CIIS) by electrocardiogram and Gensini score (Coronary Angiographic Scoring System) were utilized for assessing the severity of coronary artery disease. Results: The average level of MMP-9 was significantly higher in the case group than in the control group (396±155 ng/mL vs. 223±87 ng/mL, p<0.001) with further demonstration that MMP-9 is an independent predictor of plaque rupture (β = 0.985, p><0.001). MMP-9 is well correlated with Gensini and CIIS score (r = 0.552, p ><0.01 and r = 0.340, p><0.01, respectively). Furthermore, serum MMP-9 enzyme significantly increased in accordance with the severity of the myocardium damage (p ><0.01) by CIIS score. Conclusion: MMP-9 plays a role at pathogenesis of plaque rupture in coronary atherosclerosis.><0.001) with further demonstration that MMP-9 is an independent predictor of plaque rupture (β = 0.985, p<0.001). MMP-9 is well correlated with Gensini and CIIS score (r = 0.552, p ><0.01 and r = 0.340, p><0.01, respectively). Furthermore, serum MMP-9 enzyme significantly increased in accordance with the severity of the myocardium damage (p ><0.01) by CIIS score. Conclusion: MMP-9 plays a role at pathogenesis of plaque rupture in coronary atherosclerosis.><0.001). MMP-9 is well correlated with Gensini and CIIS score (r = 0.552, p<0.01 and r=0.340, p<0.01, respectively). Furthermore, serum MMP-9 enzyme significantly increased in accordance with the severity of the myocardium damage (p<0.01) by CIIS score. Conclusion: MMP-9 plays a role at pathogenesis of plaque rupture in coronary atherosclerosis.